Collaborating Local Government Agencies to Prevention Adolescent Reproductive Health in Makassar, Indonesia - Agus Heruanto Hadna; Nasrulhaq Nasrulhaq (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
Collaboration is an approach and concept of managing public policy in Makassar, Indonesia. Recently, the municipality of Makassar has capitalized on the collaboration of local government agencies regarding public affairs to prevent issues of Adolescent Reproductive Health (ARH). ARH is a strategic issue for local government so that it is solved collaboratively. The collaborating governmental organization comprises the Department of Education, Health, Family Planning, and all of the Urban Villages. This research employed a qualitative method focusing on the analysis of collaborative phenomena of local government agencies in Generation Planning Program through Adolescent Counseling Information Center (ACIC) and Adolescent Families Development (AFD) in Makassar. Data were obtained and analyzed in an orderly and structured manner with general qualitative approach. Based on the field research, the local government agencies collaborate in two ways. The first collaboration deals with the sectoral term which is the involvement of the government agencies related to adolescent reproductive health policy. The second collaboration deals with the regional term including the involvement of the Sub-District and Urban Villages in Makassar as grassroots bureaucracy. Collaborative themes and relations are the main findings in this article. An interesting theme in the idea of collaboration is mutual interdependence, while an exciting theme in the implementation of collaborative action is joint interaction. Organizational relationships in collaboration between local government agencies are coordination, consolidation, consultation, and command. This study concluded that sectoral and regional collaboration is proper in bringing a solution to public health affairs that are very complex.